ANALISIS PERBEDAAN KOMPETENSI SOSIAL DAN INTENSI KEWIRAUSAHAAN ANTARA MAHASISWA ETNIS JAWA DAN ETNIS MADURA DI UNIVERSITAS BRAWIJAYA - Fergiansyah, Brianditya (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research aims to know whether there is a diversity on social competence and entrepreneurial intention among Javanese and Madurese students in University of Brawijaya. This research collected data through questionnaire distribution for 100 respondents. The subject of this research was the student of Brawijaya University from two different ethnic backgrounds. There were equal number of students (50:50) of each Javanese and Madurese ethnics. The data analysis utilized t test. From the t test result, it demonstrated that need for achievement, self-efficacy, and entrepreneurial intention among Javanese and Madurese ethnics tend to be equal. Yet, from instrumental readiness and culture among Javanese and Madurese student, the diversity does occur.Keywords: social competence, intention, students, Javanese, Madurese, entrepreneurship